(untitled) (CIPEEX, 2022)
THE CURRENT GENERATION IS INCREASINGLY CONNECTED TO AUDIOVISUAL, AUDIO AND VIDEO STORAGEAND REPRODUCTION PLATFORMS, AND STREAMING FILM AND SERIES PROVIDERS, LINKED TO THE INTERNET NETWORK,WHERE MANY OF THE ANIMATED FILMS ARE INSERTED, MAKING THEM IMPORTANT AND ACCESSIBLE ELEMENTS ANDTOOLS FOR THE DESIGN OF DIDACTIC STRATEGIES IN ENVIRONMENTAL EDUCATION. THROUGH THE CINEMATOGRAPHICANIMATIONS, THE DISCREPANCY BETWEEN LEGISLATION AND THE ENVIRONMENT WILL BE SHOWN AND TOUNDERSTAND HOW THESE THEMES DIALOGUE WITH EACH OTHER IN THE SENSE OF EXPANDING THE POSSIBILITIES OFPEDAGOGICAL PRACTICE WITH THIS DIRECTION. THIS ESSAY SOUGHT TO QUANTIFY PUBLICATIONS THAT EXPLOREDISCUSSIONS ON THE RELATIONSHIP BETWEEN ANIMATED CINEMA, FILMS WITH TECHNOLOGY AND DESTRUCTION OFTHE PLANET, LEGISLATION AND ENVIRONMENTAL EDUCATION, BASED ON AN EXPLORATORY AND QUALITATIVE STUDY.THIS STUDY SHOWED THAT CINEMA IS CAPABLE OF ENRICHING PEDAGOGICAL PRACTICE AND PROMOTING REFLECTIONS,WHEN ITS LANGUAGE IS CAREFULLY EXPLORED IN THE CONTEXT OF THE DIDACTIC SITUATION, APPROACHING THE LAWSTHAT CAN BE MOST USED IN TERMS OF THE ENVIRONMENT AND SUSTAINABILITY FOR SOCIETY.